On the generating function of the time of first hitting the boundary by a semicontinuous difference of independent renewal processes with discrete time - Yezhov, I. I.; Kadankov, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For a semicontinuous difference of two independent renewal processes, we find the generating function of the time of first hitting the boundary.